The Translator’s ‘Magic’ Wand: Harry Potter’s Journey from English into French - Feral, Anne-Lise (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2006)
AbstractMuch has been written about the international phenomenon that the Harry Potter series has become and inevitably about the translations that contributed to its success. Eirlys E. Davis’s comparative analysis of some of these translations in particular shows dissimilarities between the strategies adopted in different languages and presents individual translators’ choices as inconsistent.This paper deals almost exclusively with the French translation of Harry Potter and the Philosopher’s Stone and reveals that, in the light of the ideological and cultural reality of the receiving corpus, patterns of translation techniques do appear. This paper looks at the transformative strategies and their effects in the target text, first focusing on the treatment of alien British values. Their transformation and disappearance indicate the need to produce a text morally suitable for its assumed readership: French youngsters. Indeed, it seems that the skopos of the target text – being read by French children – determined the translator’s decisions not only to smooth down extreme British otherness but also to reinforce the fantasy of Harry Potter’s world.Indeed, the French creates an utterly “other” world by strengthening its fantastic and magical aspects while undermining the sense of familiarity and credibility of the community portrayed. The shift from a child’s perspective in the original to an adult’s in the translation leads to numerous omissions of banal and realistic details, weakening the realness of the setting and the protagonists.I give textual and extra-textual examples of these transformative strategies which ultimately reduced Harry Potter à l’école des sorciers to a fairy tale and shaped the way it was perceived and received in France.